PERAN ORGANISASI NASYIATUL AISYIYAH KOTA MAKASSAR DALAM MENINGKATKAN KUALITAS DAKWAH PEREMPUAN (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This thesis discusses the role of the Nasyiatul Aisyiyah Makassar city in improving the quality of women's da’wah. This study uses a qualitative research type and is located at the Muhammadiyah Islamic da’wah center. In this study, data were compiled and collected from various sources, namely in the form of interviews, data reduction, documentation, and also observations at the research site. The results of this study indicate that 1). Nasyiatul Aisyiyah Makassar City has a work program to improve the quality of women's da’wah, such as several work programs that are directed to become Islamic, social, women's education and especially da’wah movements which are certainly very accepted by the wider community.2) The obstacles of Nasyiatul Aisyiyah Makassar City in improving the quality of women's da'wah are having limited human resources and the activities of members who are mostly workers and taking care of the household or family, lack of socialization to the community about the Nasyiatul Aisyiyah organization and limited time fo Nasyiatul Aisyiyah members.